Effect of particle size on mechanical behavior of sugarcane bagasse ash reinforced AlSi10Mg alloy. (2022) - Balaji, A.; Gomathi, K.; Naveen Rajan, U.S.; Mithil, J.; Vinunath, Aryan; Vagish, R.C.
Abstract: Fabrication of metal matrix composite is an emerging trend in the field of engineering, by following its footsteps aluminium hybrid composites are extensively used in almost all the automotive applications, because there is a significant reduction in using the actual metal as a base during manufacturing. Recently most of the research proven that the aluminium hybrid composite material has better mechanical and tribological properties compared to aluminium metal. In this work, Sugarcane bagasse ash (SCBA) was used as a reinforcement material along with magnesium. SCBA is used as a reinforcement material and its chemical composition was analysed using Energy Dispersive X-ray Spectroscopy test that shows the presence of rich silica particles. Sugarcane Bagasse is also the by-product of paper mills which are abundantly available. SCBA particles with weight percentages (i.e., 3%, 6%, 9%) are reinforced with aluminium alloy (AlSi10Mg) using stir casting process. Then the specimens were subjected to Hardness, Tensile, Impact and Pin-on disc tests. The results were compared with aluminium alloy.